2020
DOI: 10.3390/biom10081176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fe, Zn, and Cu in Pregnancy

Abstract: Iron (Fe), copper (Cu), and zinc (Zn) are microelements essential for the proper functioning of living organisms. These elements participatein many processes, including cellular metabolism and antioxidant and anti-inflammatory defenses, and also influence enzyme activity, regulate gene expression, and take part in protein synthesis. Fe, Cu, and Zn have a significant impact on the health of pregnant women and in the development of the fetus, as well as on the health of the newborn. A proper concentration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 345 publications
(355 reference statements)
1
57
0
1
Order By: Relevance
“…Increased Cu concentrations in pregnancy was also demonstrated by other authors [ 16 ], which was explained by an increase in its carrier proteins, ceruloplasmin, and elevated levels of maternal estrogens. It was also shown that, in serum of women with normal fetal development, Cu concentration was increased when compared to women with fetal developmental disorders [ 38 ]. On the other hand, it was demonstrated, that women at early stage of pregnancy with lower plasma Cu concentrations were better protected against risk for any pregnancy complication when compared with women with high plasma Cu [ 17 ], because higher concentration of Cu is associated not only with oxidative stress, but also with inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased Cu concentrations in pregnancy was also demonstrated by other authors [ 16 ], which was explained by an increase in its carrier proteins, ceruloplasmin, and elevated levels of maternal estrogens. It was also shown that, in serum of women with normal fetal development, Cu concentration was increased when compared to women with fetal developmental disorders [ 38 ]. On the other hand, it was demonstrated, that women at early stage of pregnancy with lower plasma Cu concentrations were better protected against risk for any pregnancy complication when compared with women with high plasma Cu [ 17 ], because higher concentration of Cu is associated not only with oxidative stress, but also with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It was well documented that higher concentration of Cu could have teratogenic consequences [ 39 ] due to excessive cellular oxidative damage [ 40 ]. Oxidized reactions are greatly accelerated by the presence of Cu in the Fenton reaction [ 38 ]. Copper is one of the most important transition metals involved in the production of • OH [ 16 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Pregnancy raises maternal iron demand to satisfy rising red cell volume, growing fetuses and placenta plus any expected or unanticipated blood loss at delivery. [18][19] Maternal plasma and blood levels during pregnancy are increased, and the fetus needs iron to provide itself with metabolism and oxygen and to load its rather large endogenous reserves of iron that are used during the first six months of its life. 20 Iron will reach the human body under two conditions, from the placenta during pregnancy to the wall of duodenum, and from the dietary intake to the upper part of the jejunum.…”
Section: Risk Factor For Iron Deficiency In Early Childhoodmentioning
confidence: 99%
“…[1][2][3] Approximately 3-5 g iron is present in the adult human body (44-55 mg per kg body weight in adult men & women), with hemoglobin incorporating more than 2/3, a four-unit molecule, one heme group and one protein chain that can be fully oxidized into the lungs and can be carried out by the lungs via the arteries to all cells across the body. 2,4,5 The erythrocytes contain many of the iron in the body, such as hemoglobin, whilst ferritine and hemosiderin contain many enzymes in the liver, spleen, bone marrow and myoglobin, including catalase, peroxidase and cytochrome. 3,5 The intake of iron is present in both iron to heme (10%) and those without heme (90%).…”
Section: Introductionmentioning
confidence: 99%